2021
DOI: 10.1038/s41598-021-86511-9
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms of esophageal epithelial regeneration following repair of surgical defects with acellular silk fibroin grafts

Abstract: Constructive remodeling of focal esophageal defects with biodegradable acellular grafts relies on the ability of host progenitor cell populations to repopulate implant regions and facilitate growth of de novo functional tissue. Intrinsic molecular mechanisms governing esophageal repair processes following biomaterial-based, surgical reconstruction is largely unknown. In the present study, we utilized mass spectrometry-based quantitative proteomics and in silico pathway evaluations to identify signaling cascade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(22 citation statements)
references
References 57 publications
0
22
0
Order By: Relevance
“…The critical role of PI3K/Akt signaling in SF or HA’s regulation of cellular biological functions has also been illustrated before. Gundogdu et al in their recent study demonstrated that PI3K/Akt signaling was a significant regulator in the repair process of surgical defects of esophageal epithelial tissue with SF grafts . Gemini-Piperni et al suggested that HA triggered Akt and other intracellular signaling pathways in the early process of osteoblast adhesion, which activated proteins involving cytoskeleton rearrangement, as well as induction of osteoblastic differentiation .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The critical role of PI3K/Akt signaling in SF or HA’s regulation of cellular biological functions has also been illustrated before. Gundogdu et al in their recent study demonstrated that PI3K/Akt signaling was a significant regulator in the repair process of surgical defects of esophageal epithelial tissue with SF grafts . Gemini-Piperni et al suggested that HA triggered Akt and other intracellular signaling pathways in the early process of osteoblast adhesion, which activated proteins involving cytoskeleton rearrangement, as well as induction of osteoblastic differentiation .…”
Section: Discussionmentioning
confidence: 99%
“…Gundogdu et al in their recent study demonstrated that PI3K/Akt signaling was a significant regulator in the repair process of surgical defects of esophageal epithelial tissue with SF grafts. 46 Gemini-Piperni et al suggested that HA triggered Akt and other intracellular signaling pathways in the early process of osteoblast adhesion, which activated proteins involving cytoskeleton rearrangement, as well as induction of osteoblastic differentiation. 27 In the current study, we found that the SF/HA hybrid coating significantly reactivated the DM-suppressed PI3K/Akt pathway, which exhibited the same effect as the ROS scavenger NAC.…”
Section: Discussionmentioning
confidence: 99%
“…The average log 2 fold protein expression of DEPs which were previously identified in postsurgical timepoints compared to the NSC for biological replicates (4 for each condition). The proteomics data were obtained from Gundogdu et al [8] B) Left: Scatterplot displaying the methylation difference for NSC→Day1 DMCs that fall within gene bodies, as well as the log 2 fold protein expression value for the protein encoded by the gene associated with that DMC. Orange line represents linear regression and gray shading represents 95% confidence interval.…”
Section: Promoter Methylation Is Inversely Correlated With Expression...mentioning
confidence: 99%
“…[6] Bilayer silk fibroin (BLSF) scaffolds represent an emerging platform for esophageal repair due to their high structural strength and elasticity, low immunogenicity, and tunable degradative properties, [7] These matrices have been previously demonstrated to support the formation of innervated, vascularized esophageal tissues with contractile properties sufficient for solid food ingestion in preclinical animal models. [7,8] Constructive remodeling of BLSF scaffolds is dependent on the ability of host progenitor cell populations to migrate, proliferate, and differentiate within the implant microenvironment to facilitate regeneration of functional neotissues. [7] Molecular mechanisms governing scaffold-mediated wound healing processes in the esophagus are largely unexplored.…”
mentioning
confidence: 99%
“…Evidence from lineage tracing and cell cycle tracing data in mice suggest oesophageal epithelial homeostasis is supported by a single stem population of progenitor cells stochastically producing one daughter for stem maintenance and one for subsequent differentiation [20]. When injury occurs, cells close to the wound transiently increase the production of progenitor cells, allowing for rapid replacement of the superficial layer as part of a co-ordinated set of responses involving molecular signals including, EGF, HGF/c-MET and NGF/TrkA [21,22].…”
Section: Mucosa and Submucosamentioning
confidence: 99%